2018
DOI: 10.3390/ijms19010280
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Evaluation of Turmeric Extract Incorporated Oil-in-Water Nanoemulsion

Abstract: To overcome the drawbacks of conventional drug delivery system, nanoemulsion have been developed as an advanced form for improving the delivery of active ingredients. However, safety evaluation is crucial during the development stage before the commercialization. Therefore, the aim of this study was to evaluate the cytotoxicity of two types of newly developed nanoemulsions. Turmeric extract-loaded nanoemulsion powder-10.6 (TE-NEP-10.6, high content of artificial surfactant Tween 80), which forms the optimal na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 51 publications
3
13
0
Order By: Relevance
“…Similarly, the toxicity of curcuminoid preparation was also tested for HEK-293 cells, and no significant toxicity was observed below 6.25 µg/mL or higher concentrations. These results are in agreement with the previously reported toxicity values for curcumin in NIH3T3, H9C2, and HepG2 cells [51]. Human trials using up to 8000 mg of curcumin found no evidence of toxicity [52].…”
Section: Resultssupporting
confidence: 92%
“…Similarly, the toxicity of curcuminoid preparation was also tested for HEK-293 cells, and no significant toxicity was observed below 6.25 µg/mL or higher concentrations. These results are in agreement with the previously reported toxicity values for curcumin in NIH3T3, H9C2, and HepG2 cells [51]. Human trials using up to 8000 mg of curcumin found no evidence of toxicity [52].…”
Section: Resultssupporting
confidence: 92%
“…Similarly, the toxicity of curcuminoid preparation was also tested for HEK-293 cells, and no significant toxicity was observed below 6.25 µg/ml or higher concentrations ( Supplementary Figure 1). These results are in agreement with the previously reported toxicity values for curcumin in NIH3T3, H9C2, and HepG2 cells [30]. Human trials using up to 8000 mg of curcumin found no evidence of toxicity [31].…”
Section: Toxicity Of Curcuminoids On Nci-h295r Cellssupporting
confidence: 92%
“…Moreover, formulations of curcumin with NEs significantly reduced its cytotoxicity in cells, probably because NEs decreased access of the drug to cells. [209] Vater et al compared the cytotoxicity of lecithin-based NEs with NEs based on conventional surfactants on human skin cells (primary human keratinocytens as well as fibroblasts). In addition, they evaluated the effect of the nanodroplet size in the range from 124 to 245 nm.…”
Section: Cytotoxicitymentioning
confidence: 99%